DESCENTRALIZACIÓN: IMPERATIVO PARA EL DESARROLLO HUMANO Y TERRITORIAL EQUILIBRADO CON GOBERNABILIDAD, EN UN CONTEXTO DE GLOBALIZACIÓN. UNA MIRADA DESDE CHILE - Von-Baer, Heinrich (Cuadernos de Administración, 2006)
Based mainly on a critical appreciation of the pending tasks of the development process of Chile, this essay is structured in two parts. The first one (Contextual frame), proposes two postulates of character of values, places the Human development as a value and as superior to the other analyzed dimensions of the development and discusses two obstacles to reach a total Human Development: a) the social inequalities (poverty, indigence,wage inequality, exclusion), main limit given its pronounced magnitudes in Latin America; and b) Centralism, inherited form the Napoleonic model of state-nation organization, reflection of the progressive obsolescence of the effective public institution to promote innovating initiatives of development in the subnational territories and to solve with effectiveness the demand of a society of the inserted participation in global dynamics. In such context it is postulated that there is a feedback between these two obstacles, reinforcing the vicious circle of the sub-development, which implies the necessity to impel innovating strategies able to interrupt that vicious dynamic. This means to impel structural reforms, now more urgent, given the globalization process, that, although it opens important opportunities of new development, it also generates manifold negative impacts, social and territorial inequalities, and governability problems. Between the most urgent reforms to impel (at least in the case of Chile), a substantial and maintained decentralization process is considered, accompanied by a significant fortification of the capacities in the sub-national levels (micro-local and pull-regional). In the second part (Proposals), an Alternative Model of Public Management is postulated “To decentralize the State from the Region”, whose profit is limited by deficiencies of the very own regions (a) pertinent and own knowledge (b) qualified and motivated Human Capital (c) Social Capital. As an answer to these deficiencies there are described, as an example, three initiatives in process of construction in Chile: (1) An Agreed Agenda of Decentralization Reforms (political,administrative, financial and of greater citizen participation). (2) The Regional Sinergia Network, from 20 regional universities, directed to generate knowledge from the demand of the communities and territories and to form new leaders for the local and regional development, with perspectives of student and labor mobility.(3) The installation of Regional Systems of Innovation, differentiated according to territories, based on the joint of related actors and the application of prospective instruments, territorial planning technological monitoring and social observation. Being from a different nature and a different genesis, these three initiatives are interdependent and concur to a same intention: to obtain a Human development and territorial balance, with governability, in globalization context.